A critical role for glycine transporters in hyperexcitability disorders - Harvey, Robert J.; Carta, Eloisa; Pearce, Brian R.; Chung, Seo-Kyung; Supplisson, Stéphane; Rees, Mark I.; Harvey, Kirsten (Frontiers in Molecular Neuroscience, 2008)
Defects in mammalian glycinergic neurotransmission result in a complex motor disorder characterized by neonatal hypertonia and an exaggerated startle refl ex, known as hyperekplexia (OMIM 149400). This affects newborn children and is characterized by noise or touch-induced seizures that result in muscle stiffness and breath-holding episodes. Although rare, this disorder can have serious consequences, including brain damage and/or sudden infant death. The primary cause of hyperekplexia is missense and nonsense mutations in the glycine receptor (GlyR) α1 subunit gene (GLRA1) on chromosome 5q33.1, although we have also discovered rare mutations in the genes encoding the GlyR β subunit (GLRB) and the GlyR clustering proteins gephyrin (GPNH) and collybistin (ARHGEF9). Recent studies of the Na+ /Cl--dependent glycine transporters GlyT1 and GlyT2 using mouse knockout models and human genetics have revealed that mutations in GlyT2 are a second major cause of hyperekplexia, while the phenotype of the GlyT1 knockout mouse resembles a devastating neurological disorder known as glycine encephalopathy (OMIM 605899). These findings highlight the importance of these transporters in regulating the levels of synaptic glycine.